1980
DOI: 10.1083/jcb.86.1.199
|View full text |Cite
|
Sign up to set email alerts
|

Polarization of endocytosis and receptor topography on cultured macrophages.

Abstract: In the J774 .2 macrophage cell line, microtubule disassembly by colchicine causes the polarization of membrane functions and structure. Colchicine-treated cells develop a bulge or protuberance that is bordered by microvillous membrane . The protuberance is the site of concanavalin A cap formation. The fluid pinocytosis of horseradish peroxidase and of fluorescein-and rhodamine-conjugated high molecular-weight dextrans, the adsorptive pinocytosis of concanavalin A, and the concentration and phagocytosis at 37°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

1981
1981
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 43 publications
4
23
0
Order By: Relevance
“…It is interesting that none of the organelles is found in the budding protrusion, an observation that has been made in cells that produce similar structures after colchicine treatment (31). This may result from the existence of a highly organized array of cytoskeletal compo- nents, especially microfilaments, in the protrusion that physically excludes the organelles.…”
Section: Resultsmentioning
confidence: 94%
“…It is interesting that none of the organelles is found in the budding protrusion, an observation that has been made in cells that produce similar structures after colchicine treatment (31). This may result from the existence of a highly organized array of cytoskeletal compo- nents, especially microfilaments, in the protrusion that physically excludes the organelles.…”
Section: Resultsmentioning
confidence: 94%
“…Recently, Walter et al . (42) have shown that colchicine is able to induce macrophages to accumulate phagocytic and pinocytic vesicles as well as Con A receptors into a cap structure at one pole of the cell . The primary mode of action of colchicine has been commonly considered to involve the disassembly of microtubules (4,5,22,27,44).…”
Section: Discussionmentioning
confidence: 99%
“…To test this, we incubated HeLa cells with either fluorescence-labeled transferrin or dextran. Transferrin undergoes clathrin-mediated endocytosis, whereas dextran is taken up by fluid phase endocytosis (7,64). Each of these fluorescent ligands was added to HeLa cells, which were then fixed, permeabilized, and stained with anti-M2 Abs.…”
Section: Colocalization Of Novel Cellular Protein Vpef With Vaccinia mentioning
confidence: 99%